Syntheses, structures and catalytic activity for Friedel-Crafts reactions of substituted indenyl rhenium carbonyl complexes. Issue 4 (16th February 2017) - Ma, Zhihong; Zhang, Xinli; Wang, Hong; Han, Zhangang; Zheng, Xuezhong; Lin, Jin
Abstract: The complexes [( η 5 -C9 H6 R)Re(CO)3 ] [R =  n Bu (8 ), t Bu (9 ), CH(CH2 )4 (10 ), Ph (11 ), Bz (12 ), 4-methoxyphenyl (13 ), 4-chlorophenyl (14 )] were synthesized by refluxing substituted indenyl ligands [C9 H7 R] [R =  n Bu (1 ), t Bu (2 ), CH(CH2 )4 (3 ), Ph (4 ), Bz (5 ), 4-methoxyphenyl (6 ), 4-chlorophenyl (7 )], and Re2 (CO)10 in decalin. The molecular structures of9, 10, 12, and13 were determined by X-ray diffraction analysis. These four crystals have similar molecular structures of the mononuclear carbonyl complex. In each of these molecules, Re is η 5 -coordinated to the five-membered ring of the indenyl group. Complexes8 –14 have catalytic activity for Friedel-Crafts reactions of aromatic compounds with a variety of alkylation and acylation reagents. Compared with traditional catalysts, these mononuclear metal carbonyl complexes have obvious advantages such as high activities, mild reaction conditions, high selectivity, and environmentally friendly chemistry. Abstract :